The MARECA (national study of management of breast cancer locoregional recurrence and oncological outcomes) study: National practice questionnaire of United Kingdom multi-disciplinary decision making. Issue 7 (July 2022) - Morgan, Jenna L.; Cheng, Vinton; Barry, Peter A.; Copson, Ellen; Cutress, Ramsey I.; Dave, Rajiv; Elsberger, Beatrix; Fairbrother, Patricia; Hartup, Sue; Hogan, Brian; Horgan, Kieran; Kirwan, Cliona C.; et al.
Abstract: Introduction: Evidence based guidelines for the optimal management of breast cancer locoregional recurrence (LRR) are limited, with potential for variation in clinical practice. This national practice questionnaire (NPQ) was designed to establish the current practice of UK breast multidisciplinary teams (MDTs) regarding LRR management. Methods: UK breast units were invited to take part in the MARECA study MDT NPQ. Scenario-based questions were used to elicit preference in pre-operative staging investigations, surgical management, and adjuvant therapy. Results: 822 MDT members across 42 breast units (out of 144; 29%) participated in the NPQ (February–August 2021). Most units (95%) routinely performed staging CT scan, but bone scan was selectively performed (31%). For patients previously treated with breast conserving surgery (BCS) and radiotherapy, few units (7%) always/usually offered repeat BCS. However, in the absence of radiotherapy, most units (90%) always/usually offered repeat BCS. For patients presenting with isolated local recurrence following previous BCS and SLNB (sentinel lymph node biopsy), most units (95%) advocated repeat SLNB. Where SLNs could not be identified, 86% proceeded to a four-node axillary sampling procedure. For ER positive, HER2 negative, node negative local recurrence, 10% of units always/usually offered chemotherapy. For ER positive, HER2 negative, node positive local recurrence, this recommendation increased to 64%. For triple negative breast cancer local recurrence, 90% of units always/usually offered chemotherapy. Conclusion: This survey has highlighted where consistencies and variations exist in the multidisciplinary management of breast cancer LRR. However, further research is required to determine how these management patterns influence patient outcomes, which will further refine optimal treatment pathways.